ANALYSIS OF THE EFFECT OF INVENTORY AND LEADTIME DELIVERY ON CUSTOMER SATISFACTION AT PT AISAN NASMOCO INDUSTRI - Muhammad Alfin Ilham; Niantoro Sutrisno; Dadang Surya Kencana (POLITEKNIK LP3I JAKARTA, 2026)
Purpose of this research to know the influence of inventory and delivery lead times against customers satisfaction at PT Aisan Nasmoco Industry, Bekasi Regency. This research approach is quantitative, namely a systematic, measurable and objective research method, focusing on collecting and analyzing data in the form of numbers (numerics) to test hypotheses, find relationships between variables, or describe certain patterns using statistics. The results of this study show that inventory influential significant to satisfaction customer t value = 2.092 and sig = 0.043. Lead time delivery has more influence than strong t - value = 4.741 and sig = 0.000. In general simultaneous, variables influential significant to satisfaction customers with sig value = 0.000. Coefficient value determination (R²) of 79.10% shows the contribution of inventory and delivery lead times against satisfaction customers, whereas 20.90% is influenced by other factors. Sugestion for the company to increase accuracy in planning inventory and speeding up the delivery process to maintain a level of satisfaction for optimal customers.